Influence of Price Perception and Distribution Channels on Purchase Decisions: A Study on Small-Scale Tofu Enterprises: Pengaruh Persepsi Harga dan Saluran Distribusi terhadap Keputusan Pembelian: Studi pada Usaha Tahu Skala Kecil - Chalimi, Mohamad; Purwanto, Nuri (Indonesian Journal of Law and Economics Review, 2023)
This study investigates the impact of price perception and distribution channels on purchase decisions within the context of small-scale tofu enterprises. Employing a quantitative approach, the research population comprises 100 consumers, with a sample size of 85 who have made purchases. Utilizing simple random sampling, the findings reveal significant effects of both price perception and distribution channels on purchase decisions, shedding light on crucial factors that shape consumer choices in the realm of small-scale tofu enterprises. Highlight: Quantitative Investigation: This study employs a quantitative approach to explore the impact of price perception and distribution channels on purchase decisions in the context of small-scale tofu enterprises. Consumer Sample: The research involves a sample of 85 consumers who have made purchases, providing insights into the decision-making process within this specific market segment. Influential Factors: The findings underscore the significant effects of price perception and distribution channels, offering valuable insights into the factors that play a pivotal role in shaping consumer choices within small-scale tofu enterprises. Keyword: Price Perception, Distribution Channels, Purchase Decisions, Small-Scale Tofu Enterprises, Consumer Choices